The Effect of Beehives in Preparing a Bee Family for Winter under the Stipulations of our Republic - Zokirovich, Eshdavlatov Orif; Eshboyevich, Yangiboyev Abdumalik; Marifjonovich, Xoljigitov Asqar (European Journal of Life Safety and Stability (2660-9630), 2022)
the article discusses in our country, the methods of safe removal of bee colonies from hibernation are described and the impact of beehives on hibernation is studied.